36. Uranium Deposits of the Grants Region - Vincent C. Kelley; Dale F. Kittel; Paul E. Melancon (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1968)
Uranium of the Grants region occurs predominantly in continental sandstones of the upper part of the Jurassic Morrison Formation, but significant lesser deposits are found in limestone of the Jurassic Todilto Formation and in black shale of the Cretaceous Dakota Formation. The deposits are disseminations that form runs ranging from a few hundred tons to several million tons. The ore consists mainly of uraninite, uraniferous carbonaceous material, coffinite, and such secondary oxidized minerals at tyuyamunite, carnotite, and uranophane. In sandstone, the ore runs were locallized by mudstone, interstitial carbonaceous material, and primary sand channel trends. In limestone, ore deposition was related to folds and fracture zones. The great bulk of production has come from the Ambrosia Lake mines in the Grants district and the Jackpile and Paguate mines in the Laguna district. The ores, which generally have been 0.20 to 0.30 per cent U3O8, are treated at mills operated by Kerr-McGee Corporation, Homestake-Sapin Partners, and The Anaconda Company, all in the Grants district. In 14·years after discovery in 1950, the deposits had yielded concentrates valued in excess of $800,000,000. Since deposition of the Jurassic host rocks, a geologic history involving tilting, faulting, erosion, changing ground-water environments, and oxidation has considerably influenced the existence and character of the deposits. It is evident that their ongm is not simple. However, a degree of agreement appears probable for a pre-Dakota age for the original ore runs, and, at Ambrosia Lake, two principal stages of ore formation, separated by Laramide faulting, are recognized. All earlier ores have been modified by Quaternary oxidation, solution, and enrichment during which time much secondary tyuyamunite, metatyuyamunite, carnotite were formed.